De l’étranger à l’ascendant : les perceptions suédoises des Samis à l’époque moderne (1630-1740) - Fur, Gunlög (Presses universitaires de Rennes, 2019)
Swedish perceptions of Saami people in the Early Modern Period considered them both as strangers and as subjects of the realm. Increasingly over the period, their strangeness became exoticized and even characterized as noble, while they were incorporated in the realm through an understanding of history that described them as remnants of the past. Both views demanded that they convert to Christianity and accept a Swedish legal and cultural hierarchy. The Saami people, however, challenged such interpretations, thus demonstrating how these perceptions were vehicles of colonialism rather than neutral observation.